Exposure assessment of 113 exogenous chemicals simultaneously in serum samples from children in north Shandong, China, and their association with sex, age, and body mass index - Fenghong Zhang; Danyang Wang; Mengxue Zhi; Jianshe Wang (Emerging Contaminants)
Children are particularly vulnerable to adverse effects from exposure to environmental chemicals, necessitating comprehensive assessment to mitigate health risks. In this study, we analyzed 477 serum samples from children aged 2–6 years in North Shandong, China, using liquid chromatography-mass spectrometry (LC-MS) to create an exposure profile of 184 exogenous chemicals. These chemicals encompass pesticides, pharmaceuticals, industrial and consumer chemicals, and food additives. Of these, 113 exogenous chemicals were identified above the limit of detection in the serum of at least one child participant, and 37 were detected in more than 30 % of the children. Notably, 17 of the 24 selected perfluoroalkyl and polyfluoroalkyl substances (PFAS) were detected. PFOA, PFBA, and PFHxS exhibited the highest concentrations, with geometric means of 38.11 ng/mL, 17.39 ng/mL, and 7.35 ng/mL, respectively. The elevated levels of short-chain PFBA suggests increased production and environmental release in recent years. Analysis of sex-based differences revealed significant differences in the serum levels of 11 chemicals, with nine compounds displaying higher concentrations in girls than in boys. Notably, long-chain PFAS, including PFUnDA, PFDA, and PFTrDA, were present at higher concentrations in girls, while short-chain PFHpA and PFBS were higher in boys. Additionally, serum levels of diphenyl phosphate and fipronil sulfone declined slightly with age, indicating heightened exposure risk during early childhood. Positive associations between monoethyl phthalate and fipronil sulfone concentrations with BMI categories were observed, suggesting a potential obesogenic effect of these compounds. This study provides critical insights into the profiles of exogenous chemicals in young children and highlights the need for targeted risk assessment of environmental pollutants impacting pediatric health.